Ұлттық менталитеттің әлеуметтік-философиялық тұрғыда зерттелуі - Abdildina, H.; Kulzhanova, Zh.; Sheryazdanova, G. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2019)
Abstract. To consider the national mentality as a problem of social philosophy, we focus on Kazakh philosophy as a source of our worldview. We set ourselves the task of analyzing the problem of mentality as a way of thinking people in terms of perceiving and accepting the world, the spiritual quality of people and how this problem began in our internal philosophy. The problem of mentality in the Kazakh world is considered in time and space. The mentality of the nomadic period in spatio-temporal dimensions, the mentality of the Kazakh nation, the mentality of the Soviet era or the Eurasian mentality and the concept of the Kazakh mentality, formed under conditions of modern independence, are reflected in the literature. The authors believe that the high value of the category of space in people will lead the population to a high level of tolerance, while finding the category of time in the first place will lead the population to increase activity and competition. Consequently, the nature of calm and, at the same time, ardent activity among nomads, contributed to the integration of time and space into public consciousness. The effectiveness of public opinion is characteristic of the countries of the Commonwealth, and the high role of social control indicates that people attach great importance to the education of generations. This quality, in turn, combines the desire to maintain national stability. The main goal of the article is to analyze the ideas and thoughts that mentality scholars write about the relationship between political processes. Key words: national mentality, national identity, Kazakh philosophy, spatio-temporal dimension.